Character Building with Literature: Linguistic Creativity of Helen Keller in Writing Autobiography (The Story of My Life) - Juliastuti Juliastuti (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The rapid development of online-social media has now provided greater convenience for transactions and interaction. It also greatly affects the mindset and behavior of user communication. Any information that is both positive and negative can easily be accessed by the public. And in admit or not, slowly began to change the pattern of life and thought patterns of people, especially bad language or hate speech with all the images that characterize them. The study of literature encourages empathy, tolerance for diversity, imagination and emotional intelligence which is the understanding of feelings, both of one’s own and the others and literature as a medium in increasing the higher order thinking skill. The research is qualitative and descriptive in nature.  The feminist paradigm of thought, a key framework among the poststructuralist paradigms and cognitive language are used as the conceptual framework for the execution of the research to reveal the creativity of Helen Keller. The method is qualitative descriptive. Helen Keller who after her illness, her infancy and early childhood were a succession of days of frustration become wild, unruly child" who kicked, scratched and screamed but literary works shaped her language and character into polite, creative, and empathy woman.